Implementation of an Islamic Interactive Application as an Innovative Learning Media for Islamic Religious Education: A Qualitative Case Study at SMK I Setia Darma Palembang - Muhamad Yudistira Nugraha; Anisah Azzahra; Muhammad Farhan Ferdino; Kasinyo Harto; Ummi Hiras Habisukan (Journal of Educational Sciences, 2026)
This study aims to describe the implementation of Islamic interactive applications as an innovative learning medium for Islamic Religious Education at SMK I Setia Darma Palembang. The background of this research is based on the need for learning that is adaptive to digital technological developments and capable of increasing students’ interest in religious subjects. The study employed a qualitative approach with a case study design, involving teachers and students through interviews, observations, and documentation of learning activities. The findings indicate that the implementation of the Islamic interactive application enhances learning effectiveness by increasing students’ motivation, active participation, and understanding of Islamic Religious Education materials. Interactive features such as learning videos, worship simulations, quizzes, and educational games support a shift from teacher-centered instruction to student-centered learning, with teachers acting as facilitators. The study also identifies several challenges, including limited technological devices, unstable internet connectivity, and teachers’ adaptation in integrating the application into lesson plans. This study contributes empirical evidence that Islamic interactive applications can function as an effective digital learning model to integrate Islamic values with technological innovation, particularly within vocational school contexts.